CFD Based Analysis of Resistance and Pitch Motion of Novel Flat Plate Panel Hull Vessel - Amiadji Amiadji; achmad baidowi; Irfan Syarief Arief; Fitricia Putri Ricinzky (Department of Naval Architecture - Diponegoro University, 2022)
This paper provides analysis regarding a phenomenal hull shape called flat panel concept, the flat panel hull is an axe bow vessel at the front part and semi trimaran at the stern part. This concept is for a small vessel such as fishing vessels, patrol vessels and prototypes have been built. Resistance and motion is important part of a vessel design, this paper compares a flat plate vessel with 282.56 ton displacement with a conventional vessel with the same displacement and same speed. The resistance comparison was conducted using Computational Fluid Dynamic (CFD) on each ship with a speed range of 5-10 knots of operational speed. The resistance shows that the flat panel vessel generates higher resistance compared to the conventional vessel where the difference varies from 8.388% to 19.954% depending on the speed. It also found that the pitch motion (Ry) of flat panel vessel is positive that indicates the bow draft is lower during the simulation in calm water. The highest value of pitch is 1.13 degrees measured at the amidships or zero point or -0.3 m at the bow. Two While the relative velocity or flow analysis indicates that flow of the flat panel vessel has enormous turbulence flow around the stern hull and smoother flow pattern at the bow, this may cause the increase of resistance and bow diving in calm water phenomena. However since the most accurate test is based on model test in hydrodynamic laboratory, it is recommended to conduct the comparison experiment in hydrodynamic laboratory.